Project-Task Based Learning (PROTABING) Model: Validity in Indonesian Language Learning in Senior High Schools - Jasmienti; Deswalantri; Lismay, Leli; Istiqlal, Abdul; Jambak, Ella Jeniro (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2025)
Teacher readiness and limited resources are still major obstacles in implementing the curriculum, including in learning Indonesian. Challenges such as lack of training, irrelevant materials, and the dense content of the Kurikulum 2013 encouraged the birth of the Kurikulum Merdeka, although similar obstacles still arise in learning. To overcome the problems found, one alternative that can be done is to innovate in learning. Based on this, the purpose of this study is to explain the characteristics of the Project-Task Based Learning (PROTABING) model that is valid in learning Indonesian in Secondary Schools. This research is included in the type of development research or Research and Development (R&D). In this study, the approach used is the 4-D development model developed by Thiagarajan & Semmel (1974) which consists of four main stages, namely define, design, develop, and disseminate. The instruments used are questionnaires, namely expert validation questionnaires. The instruments used are validated before use. This study produced a PROTABING model design consisting of 5 syntaxes, namely exploration, planning, implementation, monitoring and evaluation of the process, completion and presentation. The model was validated by experts and produced a valid learning model, with a validation value of material or content of 94%, presentation of 94%, language of 93%, syntax of 89%, reaction principle of 85%, social system of 88%, support system of 97%, instructional impact and accompaniment of 98%.